Penerapan Model Cooperative Learning Tipe Probing Prompting untuk Meningkatkan Hasil Belajar Kognitif Siswa Mata Pelajaran Fiqih - Anas Salahudin; Hariman Surya Siregar; Annisa Nurazizah (Mitra PGMI: Jurnal Kependidikan MI, 2021)
Learning Fiqh in class IV MI Hayatul Islam Cileat was monotonous which affected to lower cognitive learning outcomes. The purpose of this study was to determine whether the Probing Prompting type of Cooperative Learning can improve students' learning outcomes. This research was Classroom Action Research. The results of the mean score before using Probing Prompting was 57.72. In the first cycle, the teacher's activity was 79.99% while the second cycle was 89.99%. The students' activities in cycle I 79.99%, cycle II 89.99%. Student cognitive learning outcomes after using the Cooperative Learning model type Probing Prompting Learning cycle I 70.34 cycle II 82.27. The accomplishment in Cycle I 54.54%, Cycle II 95.45%. The study concluded that the Cooperative Learning type Probing Prompting model could improve student cognitive learning outcomes in fiqh subjects.